Rural land engineering and poverty alleviation: Lessons from typical regions in China - Liu, Yansui; Wang, Yongsheng (Journal of geographical sciences, 2019)
Poverty is a key issue restricting rural sustainable development; concurrently, regional land degradation impedes agricultural development and rural revitalization. China faces severe land degradation and deepening rural poverty under the context of rapid urbanization. To address these challenges, sustainable land use is an important tool in our society’s economic development. Rural engineering, including rural land consolidation, reclamation, restoration, reallocation, improvement, and development, is the most direct and effective way to achieve rural sustainable poverty alleviation. This study clarifies the framework between land engineering and rural poverty alleviation, and introduces land engineering technologies, newly created land utilization practices, and the contributions to poverty alleviation in representative degraded land regions. Land engineering can increase land quantity, improve land quality, enhance land ecological function, and promote man-land system coupling. Further, it can erase rural poverty by increasing county revenue and households’ income, lead to industrial development, and improve living environment. Specifically, degraded sandy land, gully land, hollowed construction land, and barren hilly land are transformed into productive land by improving the land structure. Innovated land engineering technologies and sustainable land utilization modes can provide the basic theories and reference approaches for rural poverty alleviation. Identifying obstacles to effective land and corresponding engineering practices are crucial to regional land exploitation and development, improving quality of life and alleviating rural poverty.